2013
DOI: 10.5433/1679-0359.2013v34n6p2853
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antibacterial activity of essential oil of a Croton rhamnifolioides leaves Pax & Hoffm

Abstract: This study describes the chemical composition and antimicrobial activity of an essential oil from the leaves of Croton rhamnifolioides Pax&Hoffm., an aromatic plant widely distributed in northeastern Brazil and commonly used in folk medicine. Eight components were identified: 1.8-cineole (46.32%) as the major compound, followed by 1-felandreno (16.70%), p-cymene (10.21%), sabinene (8.14%) and trans-caryophyllene (4.81%). The essential oil exhibited antibacterial activity against Aeromonas hydrophila, Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
1
13
0
2
Order By: Relevance
“…The chemical composition of the essential oil of Croton rhamnifolioides leaves is similar to the compounds identified in the same species by COSTA et al, (2013), presenting four constituent in common, identified by the present study: α pinene, sabinene, linalol and germacrene-D. However, in the study by this author the 1,8-cineol was identified as the major constituent.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The chemical composition of the essential oil of Croton rhamnifolioides leaves is similar to the compounds identified in the same species by COSTA et al, (2013), presenting four constituent in common, identified by the present study: α pinene, sabinene, linalol and germacrene-D. However, in the study by this author the 1,8-cineol was identified as the major constituent.…”
Section: Resultssupporting
confidence: 85%
“…In studies undertaken by COSTA et al (2013), bacterial activity of the essential oil of Croton rhamnifolioides leaves was revealed against several bacteria, amongst them S. aureus and E. Coli presenting a MIC of 5 -1 µL/mL and 20 -1 µL/mL respectively via the gas contact method. This result was attributed to the presence of 1,8-cineol, the major constituent.…”
Section: Resultsmentioning
confidence: 99%
“…The genus Croton stands out for presenting a large number of species in tropical and subtropical regions [5] and for its extensive use in traditional medicine in communities of Asia, Africa, and South America [6]. In Brazil, Croton species have been used mainly to treat inflammatory [7] and infectious [8,9] diseases. The popular use of this genus led to the development of scientific research to validate its actions.…”
Section: Introductionmentioning
confidence: 99%
“…16 Furthermore, several studies have reported the chemical characterization and biological activities of EOs extracted from Croton species. [17][18][19][20][21] In recent years, the search for efficient natural compounds with larvicidal activity against A. aegypti and low environmental toxicity has increased, thus EOs of Croton species are outstanding candidates, since they are in some cases, they are readily available, and economically viable. In fact, the larvicidal activity of EOs extracted from C. zehntneri, C. jacobinensis, C. argyrophylloides, C. sonderianus, C. nepetaefolius and C regelianus have been previously reported.…”
Section: Introductionmentioning
confidence: 99%